2006
DOI: 10.1038/sj.onc.1209361
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation and activation of PKCα by ErbB2 through Src promotes breast cancer cell invasion that can be blocked by combined treatment with PKCα and Src inhibitors

Abstract: Although ErbB2 is known to enhance breast cancer metastasis, the signaling events responsible for this remain elusive. a-Isozyme of protein kinase C (PKCa), which is involved in cancer development and progression, has been suggested to be activated by ErbB2 without direct evidence. In addition, the roles of PKCa in ErbB2-mediated cancer cell malignancy have not been clearly identified. In this study, we investigated whether ErbB2 can activate PKCa and determined what role PKCa plays in ErbB2-mediated breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 35 publications
(54 reference statements)
2
77
0
Order By: Relevance
“…We and others (Guy et al, 1992;Tan et al, 1997Tan et al, , 2005Tan et al, , 2006aTan et al, , 2006b) have previously shown that the overexpression of ErbB2 increases the transformation and/ or metastatic potentials of breast cancer cells. In addition, ErbB2 has been shown to activate signaling molecules that regulate bioenergetic metabolism, such as Ras, PI3K/Akt, mTOR and Src (Yarden and Sliwkowski, 2001;Zhou et al, 2004;Tan et al, 2005Tan et al, , 2006bZhang et al, 2007). A recent study investigated the role of lactate dehydrogenase A (LDH-A), a critical enzyme in the glycolysis pathway, in the tumor maintenance of neu-transformed mouse mammary epithelial cells, showing that compared to normal cells, cancer cells have deregulated bioenergetic metabolism and increased glycolysis (Fantin et al, 2006).…”
Section: Introductionmentioning
confidence: 69%
“…We and others (Guy et al, 1992;Tan et al, 1997Tan et al, , 2005Tan et al, , 2006aTan et al, , 2006b) have previously shown that the overexpression of ErbB2 increases the transformation and/ or metastatic potentials of breast cancer cells. In addition, ErbB2 has been shown to activate signaling molecules that regulate bioenergetic metabolism, such as Ras, PI3K/Akt, mTOR and Src (Yarden and Sliwkowski, 2001;Zhou et al, 2004;Tan et al, 2005Tan et al, , 2006bZhang et al, 2007). A recent study investigated the role of lactate dehydrogenase A (LDH-A), a critical enzyme in the glycolysis pathway, in the tumor maintenance of neu-transformed mouse mammary epithelial cells, showing that compared to normal cells, cancer cells have deregulated bioenergetic metabolism and increased glycolysis (Fantin et al, 2006).…”
Section: Introductionmentioning
confidence: 69%
“…PKCα levels may especially be increased in breast cancer patients with low or negative estrogen receptor levels (Lahn et al, 2004). Activation of PKCα by ErbB2 through Src has been shown to promote breast cancer cell invasion that can be blocked by combined treatment with PKCα and Src inhibitors (Tan et al, 2006). There is evidence that loss of PKC function contributes to the anti-proliferative action of a number of anticancer compounds (Musashi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A prior report (32) using breast cancer cell lines showed that overexpression of HER-2 led to up-regulation and activation of phosphokinase C (PKC). In breast cancer patients' samples, HER-2 overexpressing tumors showed significantly higher PKC membrane staining compared with HER-2 low expressing tumors.…”
Section: Discussionmentioning
confidence: 99%